Baseline Characteristics of the VANISH Cohort. (December 2019) - Axelsson Raja, Anna; Shi, Ling; Day, Sharlene M.; Russell, Mark; Zahka, Kenneth; Lever, Harry; Colan, Steven D.; Margossian, Renee; Hall, E. Kevin; Becker, Jason; Jefferies, John Lynn; Patel, Amit R.; et al.
Abstract : Background: The VANISH trial (Valsartan for Attenuating Disease Evolution in Early Sarcomeric Hypertrophic Cardiomyopathy) targeted young sarcomeric gene mutation carriers with early-stage hypertrophic cardiomyopathy (HCM) to test whether valsartan can modify disease progression. We describe the baseline characteristics of the VANISH cohort and compare to previous trials evaluating angiotensin receptor blockers. Methods: Applying a randomized, double-blinded, placebo-controlled design, 178 participants with nonobstructive HCM (age, 23.3±10.1 years; 61% men) were randomized in the primary cohort and 34 (age, 16.5±4.9 years; 50% men) in the exploratory cohort of sarcomeric mutation carriers without left ventricular hypertrophy. Results: In the primary cohort, maximal left ventricular wall thickness was 17±4 mm for adults and Z score 7.0±4.5 for children. Nineteen percent had late gadolinium enhancement on cardiac magnetic resonance. Mean peak oxygen consumption was 33 mL/kg per minute, and 92% of participants were New York Heart Association functional class I. New York Heart Association class II was associated with older age, MYH7 variants, and more prominent imaging abnormalities. Six previous trials of angiotensin receptor blockers in HCM enrolled a median of 24 patients (range, 19–133) with mean age of 51.2 years; 42% of patients were in New York Heart Association class ≥II, and sarcomeric mutations were not required. Conclusions: The VANISH cohort is much larger, younger, less heterogeneous, and has less advanced disease than prior angiotensin receptor blocker trials in HCM. Participants had relatively normal functional capacity and mild HCM features. New York Heart Association functional class II symptoms were associated with older age, more prominent imaging abnormalities, and MYH7 variants, suggesting both phenotype and genotype contribute to disease manifestations. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01912534. Abstract : Supplemental Digital Content is available in the text.